Human factors in the hospital: Education, skills, and job details - Kristen Webster; Laura Barg-Walkow; Sarah Fouquet (Human Factors in Healthcare, 2023)
Objective: To present the job requirements and background Human Factors professionals may need to be prepared and succeed in health care facilities. Background: Both hospitals and Human Factors professionals must be prepared for the predicted growth of Human Factors job openings in health care. Professionals transitioning from another industry or graduating from a Human Factors and Ergonomics (HFE) program may benefit from understanding what hospitals need, education requirements, and the compensatory landscape. To date, there is a lack of baseline information about Human Factors professional job details in health care. Method: We surveyed hospital-embedded Human Factors professionals. We grouped respondents based on the amount of time dedicated to operations vs. research work. Results: Of 32 respondents, 75% were women. Hospital-embedded professionals reported an average salary of $153,917 and a median salary of $149,481. Although more institutions required a master's degree, 25% of practitioners had a doctorate degree. Technical and interpersonal skills were similar between researchers and practitioners including data collection and teamwork. Conclusion: Universities can use this information to tailor educational programs for HFE students interested in a health care track. Hospitals seeking HFE professionals can create targeted job descriptions. HFE professionals can assess their ability to transition into the health care setting. Application: This information can be used by HFE professionals to assess their readiness to enter the hospital setting and negotiate compensation based on the current market. Hospitals can also use this to determine what skills HFE professionals bring.